Conservation decisions under pressure: Lessons from an exercise in rapid response to wildlife disease. Issue 1 (29th November 2019) - Canessa, Stefano; Spitzen‐van der Sluijs, Annemarieke; Stark, Tariq; Allen, Bryony E.; Bishop, Phillip J.; Bletz, Molly; Briggs, Cheryl J.; Daversa, David R.; Gray, Matthew J.; Griffiths, Richard A.; Harris, Reid N.; Harrison, Xavier A.; et al.
Abstract: Novel outbreaks of emerging pathogens require rapid responses to enable successful mitigation. We simulated a 1‐day emergency meeting where experts were engaged to recommend mitigation strategies for a new outbreak of the amphibian fungal pathogen Batrachochytrium salamandrivorans . Despite the inevitable uncertainty, experts suggested and discussed several possible strategies. However, their recommendations were undermined by imperfect initial definitions of the objectives and scope of management. This problem is likely to arise in most real‐world emergency situations. The exercise thus highlighted the importance of clearly defining the context, objectives, and spatial–temporal scale of mitigation decisions. Managers are commonly under pressure to act immediately. However, an iterative process in which experts and managers cooperate to clarify objectives and uncertainties, while collecting more information and devising mitigation strategies, may be slightly more time consuming but ultimately lead to better outcomes.